Blockchain-Based Systems Development Using Model-Driven Engineering - Velasco, Gislainy; Vaz, Noeli Antônia Pimentel; Martins, Matheus Brito; Silva, Matheus Lázaro Honório da; Silva, Pedro Moraes Ribeiro Gonçalves; Carvalho, Sergio T. (Workshop em Blockchain: Teoria, Tecnologias e Aplicações (WBlockchain), 2024)
Blockchain-based software development faces significant challenges related to decentralization, coordinating system elements across network nodes, and making complex decisions about the distribution of software components between blockchain and conventional structures. Additionally, the limitation in data storage capacity in blockchain transactions requires integrating solutions, raising critical access control issues, and removing false or legally problematic data when stored on the ledger. Identity management also undergoes transformations, with users being identified by encrypted addresses and their interactions validated by private access keys, presenting security and information recovery challenges in case of private key loss. The integration between blockchains and conventional systems becomes essential to ensure the architectural integrity of the systems. In this context, an approach is introduced for developing blockchain-based systems, focusing on integrating conventional systems through Model-Driven Engineering (MDE). The central proposal aims to fill a gap in the literature, providing a comprehensive strategy from conception to implementation in blockchain-based systems, using MDE as a software engineering technique. This work is presented as a position paper, representing an ongoing effort outlining an innovative perspective in blockchain systems development. This exploratory research project investigates potential synergies between blockchain and MDE techniques. We hope to contribute significantly to the seamless integration between blockchain and conventional systems.